Enhancing students’ poetry writing creativity and learning motivation through RADEC-based learning modules - Tatang Suryadi; Dadang Sunendar; Wahyu Sopandi; Aliefya Nurbaity (Universitas Sebelas Maret, 2026)
Poetry writing instruction in elementary schools still faces several challenges, particularly the low levels of students’ creativity and learning motivation due to the limited availability of systematic instructional materials that support the creative process. The purpose of this study is to produce a valid, effective, and tested RADEC-based module in improving students' creativity in poetry writing and their learning motivation. This study used an R&D approach with the ADDIE model. The participants included fifth-grade elementary school students, teachers, and expert validators. Data were collected through interviews, tests, questionnaires, and documentation studies. The results indicate that the developed module falls into the “very feasible” category based on expert validation. The implementation of the module showed an improvement in students’ poetry writing creativity, with the average pretest score increasing from 40.4 to 78.8 and an N-gain of 0.67 (moderate). Students’ learning motivation also increased from 54.2 to 83.4, with an N-gain of 0.65 (moderate). In addition, teacher and student responses were categorized as very positive, indicating that the module is practical and effective for classroom use. Therefore, the RADEC-based learning module is proven to be effective in enhancing elementary school students’ creativity in poetry writing and their learning motivation.